Prévalence des mammites dans les élevages de la wilaya de Mostaganem - Tedjine, Aicha (My University, 2019)
Intramammary infection is defined as the presence and multiplication of a bacterial population in one or more areas of the udder. This disease has negative economic impacts.Our study aims to start with, first of all, to identify the different bacteria that cause breast inflammation, and to determine the frequency of the germs responsible for these infections. In a second step, estimate the importance of clinical and subclinical mastitis and highlight the different factors that may increase the risk of intra-mammary infections. The somatic cell count showed strongly elevated average levels, ranging from 160,000 to 680,000 cells / ml in the tested milks. The infection affects much the hindquarters (95%) compared to the forequarters (5%) with a predominance of breast-borne germs (Staphylococcus aureus Fecal Streptococci) compared to environmental germs (Enterobacteria) that are absent.Par ailleurs, la présence de spores butyriques est constatée dans l’ensemble des laits des vaches litières des éleveurs et des collecteurs. Enfin, la prévalence des mammites est de 18,5% chez les vaches des éleveurs encadrés par les collecteurs et de 14,3% chez les vaches des éleveurs non encadrés.The poor hygienic conditions of milking, the non-control of the state of hygiene of the milking machine and the poor maintenance of the habitat, are probably the risk factors for the appearance and the persistence of infections. Breast.
Keywords: Milk cow; Clinical and subclinical mastitis; somatic cells; Bacteriology.